THE PRESENT STATUS OF ACCOUNTING TEACHING. - Greer, Howard C. (The Accounting Review, 1933)
The work of teachers of accounting in colleges or universities falls into two broad divisions. One of the two major responsibilities is the training of students, equipping them with such knowledge of accounting as will be most useful to them in the business world, in professional practice and in all the activities of life. The other of the major responsibilities is the active promotion of research in the accounting field, the determination of sound principles and practices, the development of adequate standards and the formulation of ideals which should guide all those engaged in the application of accounting to economic and social problems. In the author's opinion, accounting teachers have given greater recognition to the first of these responsibilities than to the second. Teachers have built up a great body of teaching materials, and have evolved courses of training which are extensive in their scope and intensive in their method. Conditions in the fifteen years prior to 1930 gave rise to a phenomenal growth in the teaching of accounting in colleges and universities. There are now hundreds of schools and teachers offering accounting courses, thousands of students enrolled in these courses, as of March 1933.